1981
DOI: 10.1177/004208168101700104
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Support for Local Growth Control

Abstract: It is often contended that support for local limitations on residential development results from the demands of the affluent, who wish to ensure limited access to their communities. This contention, along with alternative explanations of local growth-control support, are examined. The article explores empirical dimensions of support for elect orally induced control of residential development. A major finding, which utilizes a discriminant function analysis of a random sample survey of registered voters, is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 4 publications
2
25
0
Order By: Relevance
“…This research supports the quality of life hypothesis, which posits that a lower quality of life is associated with greater willingness to control growth (Johnston, 1980;Gottdiener and Neiman, 1981;Connerly and Frank, 1986;Anglin, 1990;Bollens, 1990;Baldassare and Wilson, 1996). As resident's quality of life decreases so did their belief that current policies to protect natural resources are adequate.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This research supports the quality of life hypothesis, which posits that a lower quality of life is associated with greater willingness to control growth (Johnston, 1980;Gottdiener and Neiman, 1981;Connerly and Frank, 1986;Anglin, 1990;Bollens, 1990;Baldassare and Wilson, 1996). As resident's quality of life decreases so did their belief that current policies to protect natural resources are adequate.…”
Section: Discussionsupporting
confidence: 68%
“…Quality of life theory implies that residents dissatisfied with their present quality of life or who predict a negative perceived change in their current quality of life would be more likely to support growth control policies (Johnston, 1980;Gottdiener and Neiman, 1981;Connerly and Frank, 1986;Anglin, 1990;Bollens, 1990;Baldassare and Wilson, 1996). From a theoretical point of view, the concept of "quality of life" is very useful in relation to land use planning.…”
Section: Introductionmentioning
confidence: 99%
“…This was indeed the case found by Knaap (1987) in terms of support for land use controls in Oregon and by Wassmer and Lascher (2006) in terms of support for regional planning in California. Other research has not found a link between level of education and support for land use policies (Gottdiener and Neiman, 1981;Protash and Baldassare, 1983;Chapin and Connerly, 2004), suggesting that this issue is not resolved. Wassmer and Lascher (2006) found that conservatives were less likely to support regional planning.…”
Section: Socioeconomic Characteristicsmentioning
confidence: 97%
“…On the other hand, when people are satisfi ed with their community, they may support land use policies in order to keep it that way (Wassmer and Lascher, 2006). In addition, those who believe that sprawl is an important problem in their community also tend to support land use policies (Gottdiener and Neiman, 1981;Connerly and Frank, 1986;Wassmer and Lascher, 2006). In general, fi ndings suggest that people support land use policies when they feel that circumstances in their community warrant government intervention.…”
Section: Community Circumstancesmentioning
confidence: 99%
“…An alternative explanation, advanced by Gottdiener and Neiman (1981), suggests that the impetus to control land use and coordinate growth using local land use controls is broadly based within a community. This sociospatial hypothesis asserts that all residents share concern over the negative externalities of rapid growth and are motivated by economic selfinterest to exercise control over "undesirable" residential development.…”
Section: Alternative Explanationsmentioning
confidence: 99%